2006
DOI: 10.28945/400
|View full text |Cite
|
Sign up to set email alerts
|

Using Podcasts as Audio Learning Objects

Abstract: Podcasting is an audio content syndication through RSS feeds in the audioblogs. As a new application of audioblogging, podcasting uses the enclosures in RSS feeds for syndication and distribution of audio content to mobile music players on the Web. Despite the advantages of podcasting, there is a need for research that focus on the use of podcasts as learning objects. Incorporating podcasts into e-learning systems require some design and translation work to achieve the pedagogical needs. This paper presents an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 1 publication
7
75
0
4
Order By: Relevance
“…Cebeci and Tekdal (2006) argued that podcasts make materials accessible to a wider diversity of learners. Evans's (2008) findings were consistent with this.…”
Section: Discussionmentioning
confidence: 99%
“…Cebeci and Tekdal (2006) argued that podcasts make materials accessible to a wider diversity of learners. Evans's (2008) findings were consistent with this.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that short podcasts (max 10-15 min) are more effective for learning than a single long unit. Long podcasts may decrease attention, thus reducing comprehension (Cebeci & Tekdal, 2006;Ormond, 2008). When podcasting is used for educational purposes, wellstructured short podcasts (following the structure of a document -i.e., converting each section into one podcast) facilitate exploration and internal searches.…”
Section: A Web Tool Transforming Digital Documents To Structured Audimentioning
confidence: 99%
“…In [4] authors combine sophisticated speech-processing techniques (including audio-based skimming) to create a multimedia player which allows audio-centered browsing and navigation of recorded presentations. However these systems require interaction with a PC and thus are not suitable for Mobile Learning.…”
Section: Related Workmentioning
confidence: 99%
“…For many people, listening may be more attractive and less tedious than reading [4], [10]. Podcasts are often used for additional support in teaching and learning.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation